2017
DOI: 10.1002/etc.4009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative copper sensitivity between life stages of common subantarctic marine invertebrates

Abstract: The development of environmental guidelines in the Antarctic and subantarctic is essential, because expansion of research, tourism, and fishing is placing these regions at increasing risk of contamination. Data are currently insufficient to create the region-specific guidelines needed for the unique conditions in these areas. To develop the most appropriate environmental guidelines, data from the most sensitive life stages of a species should be included to ensure effective protection throughout its life cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…For many species, 4 d was the minimum duration required to see a substantial effect on mortality, and was reported in the present study, because this is commonly used in tests with temperate species. A test duration of 10 d has previously been used in tests with Antarctic and subantarctic species (e.g., Payne et al ; Marcus Zamora et al ; Holan et al , , ), and provides a good compromise between the shortest duration required to consistently see a response, and the extended duration that is appropriate for cold‐climate species with slow metabolic rates. For some cold‐climate species, even longer test durations (up to 4 wk) have been used (e.g., Sfiligoj et al ; Brown et al ) and may have provided more sensitive results, but, to be in keeping with the premise of the rapid method, these durations were impractical and beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 99%
“…For many species, 4 d was the minimum duration required to see a substantial effect on mortality, and was reported in the present study, because this is commonly used in tests with temperate species. A test duration of 10 d has previously been used in tests with Antarctic and subantarctic species (e.g., Payne et al ; Marcus Zamora et al ; Holan et al , , ), and provides a good compromise between the shortest duration required to consistently see a response, and the extended duration that is appropriate for cold‐climate species with slow metabolic rates. For some cold‐climate species, even longer test durations (up to 4 wk) have been used (e.g., Sfiligoj et al ; Brown et al ) and may have provided more sensitive results, but, to be in keeping with the premise of the rapid method, these durations were impractical and beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Test methodologies based on previous work were used for 7 species: Zaus sp., T. angulatus , Laevilitorina caliginosa , M. hamiltoni , G. trapesina , and O. ohlini (Holan et al 2016, 2017, 2018, 2019), and E. gigas (Lewis et al 2016). For the remaining 4 species, test methodologies were developed during the present study (full test method details are available in King et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It is commonly recognized that early-life stages are usually more sensitive than adult organisms of the same species, but exceptions do exist. Holan et al (2018) found adult individuals of the marine bivalve Gaimardia trapesina to be more sensitive than juveniles when exposed to copper (Holan et al 2018). Since one of the overarching goals of the derivation of EQS is to protect species at a population level, there is no clear reason for not including acute EC 10 values in the derivation of the AA-EQS.…”
Section: Using Acute Ec 10 Values For Eqs Derivationmentioning
confidence: 99%